Proposal for implementation of a ranking model for Olympic Taekwondo competitions using PageRank - Kim, E.; Jeon, M. (International Journal of Performance Analysis in Sport, 2019)
In this study, a PageRank model is proposed to overcome the existing problems in estimating the Olympic Taekwondo rankings. For this purpose, PageRank value was calculated by using the results of 144 matches in the Men`s -58 kg class at the World Gran Prix Taekwondo competition. As a result, we identified the possibility of applying the PageRank model to calculate the Olympic Taekwondo ranking. In addition, there was a difference between the rankings calculated by the PageRank method and the Accumulative Point Index System method which is currently used, and the PageRank method was found to be more validity.